2015
DOI: 10.1016/j.nmd.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the DcpS inhibitor D156844 on the protective action of follistatin in mice with spinal muscular atrophy

Abstract: Spinal muscular atrophy (SMA), a leading genetic cause of pediatric death in the world, is an early-onset disease affecting the motor neurons in the anterior horn of the spinal cord. This degeneration of motor neurons leads to loss of muscle function. At the molecular level, SMA results from the loss of or mutation in the survival motor neuron 1 (SMN1) gene. The number of copies of the nearly duplicated gene SMN2 modulates the disease severity in humans as well as in transgenic mouse models for SMA. Most precl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The rho kinase inhibitor Y-27632 ameliorates the phenotype of SMA mice independent of SMN expression (Bowerman et al, 2010). Follistatin increases the lifespan of SMNΔ7 SMA mice (Harris and Butchbach, 2015; Rose Jr et al, 2009). This recombinant protein does not increase SMN expression in vivo suggesting that its effects are independent of SMN (Rose Jr et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The rho kinase inhibitor Y-27632 ameliorates the phenotype of SMA mice independent of SMN expression (Bowerman et al, 2010). Follistatin increases the lifespan of SMNΔ7 SMA mice (Harris and Butchbach, 2015; Rose Jr et al, 2009). This recombinant protein does not increase SMN expression in vivo suggesting that its effects are independent of SMN (Rose Jr et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of different classes of small cell permeable compounds has been examined on increasing levels of SMN protein by enhancing transcription that improve disease phenotype in mice with SMA. These compounds include quinazoline compounds (eg, RG3039) that function as inhibitors of RNA decapping enzyme (DcpS) [26][27][28] and have been shown to improve the disease phenotype, including the lifespan of mice with SMA in different SMA mouse models, severe SMAD7 model [29][30][31] and intermediate Smn 2B/model. 32 Benefits of RG3039 treatment were observed in the improvement of SMA phenotype, such as increase in the number of spinal motor neurons and increase in the number of SMNcontaining gems.…”
Section: Regulation Of Smn2 Gene Expressionmentioning
confidence: 99%
“…The severity of SMA has so far indicated that there is a relatively short therapeutic window to achieve a maximal effect, however, adjunctive or combinatorial strategies may expand this window, thereby increasing the number and the types of patients that respond to drugs. (26)(27)(28)(29)(48)(49)(50)(51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%